The Trinitarian theology of Hans Urs Von Balthasar : an Introduction - McInerny, Brendan (University of Notre Dame Press, 2020)
"Although scholarship has long recognized the centrality of the Trinity in the theology of Hans Urs von Balthasar, no sustained treatment of this theme has been undertaken. In this insightful new study, Brendan McInerny fills this gap, situating Balthasar's Trinitarian theology in conversation both with the wider Christian theological tradition and with his non-Christian intellectual contemporaries. Drawing from across Balthasar's extensive body of works, McInerny argues that Balthasar's vivid description of the immanent Trinity provides a way to speak of how "God is love" in himself, beyond his relationship to creatures. He then shows how Balthasar's speculation into the immanent Trinity serves as the substructure of his theology of deification. For Balthasar, what we say about the inner life of God matters because we are called to share in that very life through Christ and the Holy Spirit, to the glory of God the Father. Finally, responding to the criticisms that Balthasar's speculations into the inner life of God are without warrant, McInerny argues that Balthasar's bold Trinitarian claims are actually a vehicle for apophatic theology. Balthasar's vivid description of the triune God does not transgress the boundaries of theological discourse. Rather, it manifests God's ever-greater incomprehensibility through verbal excess, oxymoron, and paradox"--